2007
DOI: 10.2500/ajr.2007.21.3087
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Nasal Obstruction Causes Daytime Sleepiness and Decreased Quality of Life Even in the Absence of Snoring

Abstract: Induction of sleep-disordered breathing (SDB) is a possible cause of excessive daytime sleepiness and impaired QOL in subjects with nasal obstruction. A variant of SDB such as silent upper respiratory resistance syndrome may participate in this phenomenon in the absence of snoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 27 publications
(30 reference statements)
1
26
0
Order By: Relevance
“…Secondly, presence of snoring in subjects with nasal congestion had an additive effect on daytime sleepiness. Similar findings were seen in a large sample of Japanese workers where chronic nasal blockage, even in the absence of snoring, was associated with higher ESS score and reduced quality of life and presence of snoring increased these effects [8].…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Secondly, presence of snoring in subjects with nasal congestion had an additive effect on daytime sleepiness. Similar findings were seen in a large sample of Japanese workers where chronic nasal blockage, even in the absence of snoring, was associated with higher ESS score and reduced quality of life and presence of snoring increased these effects [8].…”
Section: Discussionsupporting
confidence: 71%
“…A number of studies have shown an adverse impact of nasal congestion on sleep quality resulting in daytime fatigue and sleepiness [8,19]. Nasal congestion has a circadian pattern and is worse in supine position, thereby Association of self-reported nasal congestion and snoring with ESS score 10 Self-reported nasal congestion Subjects with ESS score 10 or above (%) Non-snorer Snorer Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The negative influence of nasal mucosal disease on quality of life has been extensively documented. [8][9][10][11][12][14][15][16] On the other hand, the condition may frequently be trivialized and/or unrecognized. 15,16 Because most of these patients benefit from medical treatment, proper diagnosis and, when indicated, initiation of medical therapy should be implemented in the preoperative assessment of every patient undergoing esthetic nasal operation.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the latter can be addressed during RP without interfering with nasal esthetics. 6,7 The negative influence of functional nasal pathology on patients' quality of life and on satisfaction after RP has already been established, [1][2][3][8][9][10][11][12][13] emphasizing the importance of a thorough preoperative evaluation of the nose in every patient seeking esthetic RP.…”
mentioning
confidence: 99%